Measuring ICT literacy among the underserved urban poor children: case study of Rumah Titian Kaseh / Muhammad Azim Hamir - Hamir, Muhammad Azim (2016)
The Malaysia government has taken many initiatives to promote Information and Communication Technology (ICT) among its citizen, which also include the underserved urban poor community, especially children. The objectives of this study is to identify the level of ICT literacy among the underserved urban poor children at Rumah Titian Kaseh and to investigate if there is any impact of Jalinan Transformasi IT Program with the urban poor children's attitude towards online tutor. The program was organized with the intention to help urban poor children literate with online tutor by providing IT course and learning materials. This research used qualitative and quantitative approach, where questionnaires were distribute to the respondents before and after they join the program, and few interview session with the urban poor children after the program ended. In order to achieve the objective of this research, Theory of Planned Behavior model was adopted to investigate the impact of the program towards the urban poor children. 25 children who joined the program was selected as respondents. The findings revealed that the ICT literacy level of the children was high and the program do have an impact with the urban poor children's attitude towards online tutor. The theory showed that intervention do affects children's perception to perform specific behavior such as online tutor. These results can help other ICT literacy program organizer to organize an effective program in increasing ICT literacy among other urban poor children.